2016
DOI: 10.1007/s00253-016-7777-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and function of prevalent symbiotic marine bacteria in the genus Endozoicomonas

Abstract: Endozoicomonas bacteria are emerging as extremely diverse and flexible symbionts of numerous marine hosts inhabiting oceans worldwide. Their hosts range from simple invertebrate species, such as sponges and corals, to complex vertebrates, such as fish. Although widely distributed, the functional role of Endozoicomonas within their host microenvironment is not well understood. In this review, we provide a summary of the currently recognized hosts of Endozoicomonas and their global distribution. Next, the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
233
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 255 publications
(251 citation statements)
references
References 70 publications
(117 reference statements)
17
233
1
Order By: Relevance
“…Similarly, in our current study the stable bacterial community of P. verrucosa was driven by the prevalence and dominance of two Endozoicomonas OTUs. Importantly, the same two Endozoicomonas phylotypes were previously shown to prevail in the microbiome of P. verrucosa across its entire global distribution range with little geographic partitioning, suggesting a particularly intimate and conserved host‐microbe relationship (Neave, Apprill, Ferrier‐Pagès, & Voolstra, 2016). …”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Similarly, in our current study the stable bacterial community of P. verrucosa was driven by the prevalence and dominance of two Endozoicomonas OTUs. Importantly, the same two Endozoicomonas phylotypes were previously shown to prevail in the microbiome of P. verrucosa across its entire global distribution range with little geographic partitioning, suggesting a particularly intimate and conserved host‐microbe relationship (Neave, Apprill, Ferrier‐Pagès, & Voolstra, 2016). …”
Section: Discussionmentioning
confidence: 64%
“…More generally, Endozoicomonas are commonly assumed to provide an important role in coral holobiont functioning due to their widespread prevalence and high abundance in many coral species (Bayer et al., 2013; Gignoux‐Wolfsohn, Aronson, & Vollmer, 2017; Glasl et al., 2016; Jessen et al., 2013; Meyer, Gunasekera, Scott, Paul, & Teplitski, 2016; Neave et al., 2016; Neave, Rachmawati, et al., 2017) and apparent metabolic versatility (Ding, Shiu, Chen, Chiang, & Tang, 2016; Hyun et al., 2014; Neave, Michell, et al., 2017; Yang et al., 2010). Further, reductions in the abundance of Endozoicomonas in stressed, diseased, or bleached corals are reported in a number of studies, suggesting that pervasive abundance of Endozoicomonas might be an indicator of habitat suitability (Bourne et al., 2008; Cárdenas et al., 2012; Gignoux‐Wolfsohn et al., 2017; Meyer et al., 2016; Morrow et al., 2014; Roder et al., 2015; Röthig et al., 2016; Ziegler et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Spongiobacter, " now recognized as belonging to the genus Endozoicomonas (Neave et al, 2016), was originally recovered from a marine sponge (Pike et al, 2013) but is also present in many gorgonian (Sunagawa et al, 2010;La Rivière et al, 2013) and scleractinian corals (Raina et al, 2009;Blackall et al, 2015;Bourne et al, 2016). "Spongiobacter" strains have been attributed a number of ecological roles; "Spongiobacter" strains from A. millepora demonstrated a dependence on DMSP and consequently a role in the biogeochemical sulfur cycle was postulated (Raina et al, 2009), whereas, "Spongiobacter" strains from the sponge Suberites carnosus demonstrated antibacterial activity (Flemer et al, 2012).…”
Section: Isolated Bacteriamentioning
confidence: 99%
“…In summer, we also observed a lower abundance of Thalassospira, known as potential symbionts of ctenophores (Hao, 2014), and four OTUs of Endozoicomonas, a genus commonly found in healthy corals (Bayer et al, 2013a,b;Neave et al, 2017;van de Water et al, 2017van de Water et al, , 2018b, as well as in a wide range of other marine invertebrates (Forget and Juniper, 2013;Fiore et al, 2015;Katharios et al, 2015). Although their exact functions are unknown, both Thalassospira and Endozoicomonas may be involved in host health through nutrient acquisition and provision, and in structuring of the host microbial community (Hao, 2014; reviewed by Neave et al, 2016). Our results on the abundance of Endozoicomonas, and the observed changes in host physiology between summer and winter, however, do not appear to provide additional insights into the potential role of Endozoicomonas in corals.…”
Section: Seasonality Has Higher Impact On Coral Holobiont Than Uv Radmentioning
confidence: 99%